PENGARUH PEMBERIAN DOSIS PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) LOKAL BUTON MENGGUNAKAN MULSA PLASTIK - KIMA, MUHAMAD RABIDIN; NURMAS, ANDI; SUBAIR, IMRAN (Jurnal Agroteknos, 2022)
This study aims to determine the effect of cow manure application on the growth and production of shallots. The research was conducted at the Field Laboratory of Experimental Gardens II, Faculty of Agriculture, Halu Oleo University, Kendari, at an altitude of 25 meters above sea level, from November to January 2022. The study used a one-factor Randomized Block Design (RBD) consisting of seven treatments. B0 (without treatment), B1 (cow manure 12.5 t ha-1), B2 (cow manure 15 t ha-1), B3 (cow manure 17.5 t ha-1), B4 (cow manure 20 t ha-1), B5 (cow manure 20 t ha-1), and B6 (cow manure 25 t ha-1). Each treatment was repeated four times so that there were 28 experimental units. Variables observed were plant height, number of leaves, number of tillers, number of tubers, plant fresh heavy, plant dry weight, tuber fresh heavy and productivity. The results showed that the dose of cow manure on the growth and yield of local Buton shallots had a significant effect on all growth and yield variables of the Buton local shallots. The best treatment was obtained at a dose of cow manure 25 t ha-1 with a plant height of 29.36 cm, number of leaves 15.00 strands, number of tillers 6.00 tillers, number of tubers 7.00, plant fresh heavy 24.62 g, weight dry plant 1.59 g, tuber fresh heavy 166.70, and productivity 1.67 t ha-1.